Environmental Monitoring of the Coal Cluster in Transition to Sustainable Development - Scherbenko Eva; Gasanov Eyvaz; Tyulenev Maxim; Kovalevsky Sergey; Rybár Radim; Lopukhinsky Leonid (E3S Web of Conferences, 2021)
The transition to sustainable development implies the spread of new environmental management standards in all industrial sectors – extractive, processing, high-tech, and infrastructure branches. This means that the industries traditionally engaged in the extraction of minerals (coal, ore, oil and gas, etc.) should take a direct part in the process of reducing land use, restoring disturbed landscapes and water bodies, reducing harmful emissions. At the same time, the mining complex is faced with the task of meeting the constantly growing needs of humanity for modern goods and services, the production of which, one way or another, requires an increase in the extraction of natural resources. In this regard, the article considers the monitoring of natural resources as a starting point for the transition of regional production systems to sustainable development. The study was based on the largest Russian coal cluster Kuzbass. The system for monitoring natural resources at the regional cluster level is considered.